Characteristics of n-Type Junctionless Poly-Si Thin-Film Transistors With an Ultrathin Channel - Lin, Horng-Chih; Lin, Cheng-I; Huang, Tiao-Yuan (My University, 2012)
In this letter, we study the characteristics of n-type junctionless (JL) poly-Si thin-film transistors (TFTs) with an ultrathin and heavily phosphorous doped channel. The fabricated devices show excellent performance with a subthreshold swing of 240 mV/dec and an on/off current ratio of > 10(7). Moreover, the JL device shows 23 times increase in the ON-state current at a gate overdrive of 4 V as compared with the conventional control device with an undoped channel. The significant improvement in the current drive is ascribed to the inherently high carrier concentration contained in the channel of the JL device. These results evidence the great potential of the JL poly-Si TFTs for the manufacturing of future 3-D and flat-panel electronic products.
Keywords: Junctionless (JL); poly-Si; thin-film transistor (TFT)